Predictive accuracy of the Violence Risk Assessment Checklist for Youth in acute institutions: A prospective naturalistic multicenter study - Anniken Lucia Willumsen Laake; John Olav Roaldset; Tonje Lossius Husum; Stål Kapstø Bjørkly; Carina Chudiakow Gustavsen; Sara Teresia Grenabo; Øyvind Lockertsen (European Psychiatry)
Abstract Background Acute health and social services for children and adolescents often struggle with youth aggression and violence. Early identification of violence risk during institutional stay can help prevent violent incidents. As such, this study assessed the predictive accuracy of the Violence Risk Assessment Checklist for Youth (V-RISK-Y) aged 12–18 in two different juvenile settings providing 24-hour services for youth. Institutions were included from child and adolescent inpatient psychiatry and residential youth care under child protective services.